2016
DOI: 10.1371/journal.pone.0158678
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Self-Report Measure of Mentalizing: The Reflective Functioning Questionnaire

Abstract: Reflective functioning or mentalizing is the capacity to interpret both the self and others in terms of internal mental states such as feelings, wishes, goals, desires, and attitudes. This paper is part of a series of papers outlining the development and psychometric features of a new self-report measure, the Reflective Functioning Questionnaire (RFQ), designed to provide an easy to administer self-report measure of mentalizing. We describe the development and initial validation of the RFQ in three studies. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
713
11
33

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 523 publications
(801 citation statements)
references
References 93 publications
44
713
11
33
Order By: Relevance
“…Another limitation might be that only self-report measures were used and patients might produce biased judgments of their own self-efficacy or mentalizing abilities. Nevertheless, previous studies showed that self-reports can be used to assess mentalizing abilities reliably and validly [34,43,44]. A further shortcoming is that only two psychological factors (mentalization and self-efficacy) were evaluated as mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation might be that only self-report measures were used and patients might produce biased judgments of their own self-efficacy or mentalizing abilities. Nevertheless, previous studies showed that self-reports can be used to assess mentalizing abilities reliably and validly [34,43,44]. A further shortcoming is that only two psychological factors (mentalization and self-efficacy) were evaluated as mediators.…”
Section: Discussionmentioning
confidence: 99%
“…The Reflective Functioning Questionnaire, brief version (RFQ) (Badoud et al, 2015;Fonagy et al, 2016) was employed to assess RF, and more specifically the self-reported tendency to consider information on intentional mental states as relevant in understanding one's and others' behaviors, adapted from the self-report developed in English . It included eight items (e.g.…”
Section: Assessment Of Mentalizingmentioning
confidence: 99%
“…The main objective of this study was to examine the potential involvement of impairments of RF/mentalizing, as measured by the Reflective Functioning Questionnaire (RFQ) (Badoud et al, 2015;Fonagy et al, 2016), in a sample of adults suffering from ADHD.…”
mentioning
confidence: 99%
“… * Includes aspects of both body and mind ** May be present and experienced on the self-engagement level, but need to be consciously expressed for it to be measured. 1 (Bradley & Lang, 1994) 2 (Allen, Chambers, & Towers, 2007) 3 (Miller, Maletic, & Raison, 2009) 4 (Lane, Quinlan, Schwartz, Walker, & Zeitlin, 1990) 5 (Benjamin, 1995) 6 ( Politi, Enright, & Weihs, 2007) 7 (Carlson & Brown, 2005) 8 (Bond et al, 2011) 9 (Fonagy et al, 2016) 10 (Jackson & Marsh, 1996) 11 (Falkenström, Hatcher, & Holmqvist, 2015) 12 (Hatcher & Gillaspy, 2006) 13 (Klein, Mathieu-Coughlan, & Kiesler, 1986) 14 (Babyak, Snyder, & Yoshinobu, 1993) 15 (Snyder, 1995) 16 (Tsai, Knutson, & Fung, 2006) 17 (Fegg, Kramer, Bausewein, & Borasio, 2007) 18 (Eriksson & Lindström, 2006) …”
Section: Tablementioning
confidence: 99%
“…Unlike many human beings, the art can tolerate such expression and can provide the sense of both being understood and being assisted in the ability to process difficult mental states. Mentalization can be measured with the Reflective Functioning Questionnaire (Fonagy et al, 2016). …”
Section: Tactile Engagementmentioning
confidence: 99%